Penerapan Birrul Waalidain Pada Pendidikan Keluarga Melalui Kegiatan Wirid Yasin Di Kelurahan Tualang Perbaungan - Siti Amalia Putri; Susanti Nirmalasari; Irwansyah Irwansyah (Journal of Innovative and Creativity, 2025)
This research aims to: (1) analyze the concept of Birrul Walidain (devotion to parents) in family education in Tualang Perbaungan Subdistrict, (2) explore the implementation of Wirid Yasin as a religious activity within the community, and (3) identify the supporting and inhibiting factors in the application of Birrul Walidain through Wirid Yasin activities. This study employed a qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that: (1) the concept of Birrul Walidain in family education serves as a foundational element in shaping the Islamic character of children. Teaching devotion and respect toward parents contributes not only to character development but also to family harmony and happiness; (2) Wirid Yasin activities are not only routine religious gatherings but also serve as a medium to strengthen social and familial ties within the community; (3) supporting factors in implementing Birrul Walidain through Wirid Yasin include strong community awareness of religious values and the proactive role of Wirid Yasin leaders in delivering religious messages. However, inhibiting factors include limited youth involvement, the influence of modern technology, and time constraints faced by families. This research emphasizes the importance of integrating religious traditions into family education and highlights the role of community-based religious activities in promoting core Islamic values.